Portfolio Analysis of Power Plant Technologies A Simulation Approach to Rebalance Fuel Mix Strategies - Rothe, Sebastian. (Edition KWV, 2011)
The liberalization process, tightening environmental standards and the need for replacing aged power plants force European utilities to optimize their future generation mix. Power plants are real assets and as a consequence the power plant park of a utility firm equals a portfolio of different generation assets. This thesis adds to the understanding how to identify an efficient generation portfolio through time by assuming a non-constant feasible set. According to our results a combination of conventional thermal and renewable energies turn out to be efficient in terms of expected value and risks. Therefore, implementing a strategy based on renewable energies which cause less CO2 per MWh generated electricity clearly pays off. Potential readership includes scholars from energy economics and energy finance as well as interested practitioners involved in these areas.